Prognostic value of adrenal gland volume after cardiac arrest: Association of CT-scan evaluation with shock and mortality. (August 2018) - Mongardon, Nicolas; Savary, Guillaume; Geri, Guillaume; El Bejjani, Marie-Rose; Silvera, Stéphane; Dumas, Florence; Charpentier, Julien; Pène, Frédéric; Mira, Jean-Paul; Cariou, Alain
Abstract: Background: Adrenal gland volume is associated with survival in septic shock. As sepsis and post-cardiac arrest syndrome share many pathophysiological features, we assessed the association between adrenal gland volume measured by computerized tomography (CT)-scan and post-cardiac arrest shock and intensive care unit (ICU) mortality, in a large cohort of out-of-hospital cardiac arrest (OHCA) patients. We also investigated the association between adrenal hormonal function and both adrenal gland volume and outcomes. Patients and Methods: Prospective analysis of CT-scan performed at hospital admission in patients admitted after OHCA (2007–2012). A pair of blinded radiologist calculated manually adrenal gland volume. In a subgroup of patients, plasma cortisol was measured at admission and 60 min after a cosyntropin test. Factors associated with post-cardiac arrest shock and ICU mortality were identified using multivariate logistic regression. Results: Among 775 patients admitted during this period after OHCA, 138 patients were included: 72 patients (52.2%) developed a post-cardiac arrest shock, and 98 patients (71.1%) died. In univariate analysis, adrenal gland volume was not different between patients with and without post-cardiac arrest shock: 10.6 and 11.3 cm 3, respectively (p = 0.9) and between patients discharged alive or dead: 10.2 and 11.8 cm 3, respectively (p = 0.4). Multivariate analysis confirmed that total adrenal gland volume was associated neither with post-cardiac arrest shock nor mortality. Neither baseline cortisol level nor delta between baseline and after cosyntropin test cortisol levels were associated with adrenal volume, post-cardiac arrest shock onset or mortality. Conclusion: After OHCA, adrenal gland volume is not associated with post-cardiac arrest shock onset or ICU mortality. Adrenal gland volume does not predict adrenal gland hormonal response.